Genome-Wide Transcriptional Excavation of Dipsacus asperoides Unmasked both Cryptic Asperosaponin Biosynthetic Genes and SSR Markers - Wang, Jian-ying; Liang, Yan-li; Hai, Mei-rong; Chen, Jun-wen; Gao, Zheng-jie; Hu, Qian-qian; Zhang, Guang-hui; Yang, Sheng-chao (Frontiers in Plant Science, 2016)
Background: Dipsacus asperoides is a traditional Chinese medicinal crop. The root is generally used as a medicine and is frequently prescribed by Chinese doctors for the treatment of back pain, limb paralysis, flutter trauma, tendon injuries and fractures. With the rapid development of bioinformatics, research has been focused on this species at the gene or molecular level. For purpose of fleshing out genome information about Dipsacus asperoides, in this paper we conducted transcriptome analysis of this species. Principal Findings: To date, many genes encoding enzymes involved in the biosynthesis of triterpenoid saponins in D.asperoides have not been elucidated. Illumina paired-end sequencing was employed to probe Dipsacus asperoides’s various enzymes associated with the relevant mesostate. A total of 30, 832,805 clean reads and de novo spliced 43,243 unigenes were obtained. Of all unigenes, only 8.27% (3578) were successfully annotated in total of seven public databases: Nr, Nt, Swiss-Prot, GO, KOG, KEGG and Pfam, which might be attributed to the poor studies on D. asperoides. The candidate genes encoding enzymes involved in triterpenoid saponin biosynthesis were identified and experimentally verified by reverse transcription qPCR, encompassing nine cytochrome P450s and seventeen UDP - glucosyltransferases. Specifically, unearthly putative genes involved in the glycosylation of hederagenin were acquired. Simultaneously, 4490 SSRs from 43,243 examined sequences were determined via bioinformatics analysis. Conclusion: This study represents the first report on the use of the Illumina sequence platform on this crop at the transcriptome level. Our findings of candidate genes encoding enzymes involved in Dipsacus saponin VI biosynthesis provide novel information in efforts to further understand the triterpenoid metabolic pathway on this species. The initial genetics resources in this study will contribute significantly to the genetic breeding program of Dipsacus asperoides, and are beneficial for clinical diagnosis and treatment.